Assessment of the Use of Forward Sale for Property Transaction in Lagos State, Nigeria - Olayinka OLOKE; Nelson AKINDELE; Peter ADERONMU (Communications of International Proceedings, 2020)
The study assesses the use of forward sale for housing delivery in Lagos state. The research was conducted to explore forward sale as a veritable instrument for reducing housing deficit in the State. The study was a survey research that involved the use of structured questionnaires administered to property developers, prospective buyers and estate surveyors and valuers. Data analysis was achieved using descriptive statistics and relative importance index while Student’s T-Test was used to test the hypothesis of the study. The result of the T-test clearly showed that forward sale is not popular among prospective home buyers in Lagos state, although it is a preferred funding option among by developers. The study further revealed that insecurity of prospective buyer’s interest, developer’s default, poor construction standard and poor workmanship are key factors influencing potential buyer’s decision to commit to forward sale arrangement. The study therefore recommends government regulation of forward sale market for the purpose of boosting buyer’s confidence.
Keywords: forward sale; finance; housing; property; strategies